Budget Policy as an Instrument of Socio-Economic Development of the Country (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article defined the essence of fiscal policy in Ukraine. Analyzed the state and effectiveness of its implementation at the present stage of social - economic development. Particular attention is paid to macroeconomic indicators characterizing the effectiveness of fiscal policy. Identified problems in the implementation of fiscal policy and effective ways to budget policy of Ukraine in the coming years.
Keywords: fiscal policy, budget, gross domestic product, deficit of budget, income and expenses budget